PENERAPAN SISTEM INFORMASI MANAJEMEN UNTUK MENINGKATKAN PENGAMBILAN KEPUTUSAN STRATEGIS DALAM ORGANISASI BISNIS - Amirulah Kaharudin; Ines Heidiani Ikasari (CV. Multi Kreasi Media, 2023)
The purpose of this research is to analyze the application of management information systems to improve strategic decision making in business organizations. The research method used is a literature review study with content analysis techniques. The results of this study include, first, important things that need to be considered in practice (design as a tool, adequate quality of decision makers; knowledge from various scientific disciplines; information from management information systems must be information that is accurate, timely, relevant , complete and economical; involvement of all members of the business organization) and secondly, the benefits of implementing (increasing profits and reducing costs of business organizations; increasing efficiency, effectiveness and excellence of business organizations; solving problems in business organizations) Management Information Systems in improving decision making strategy in business organizations.